The rapid developmental rise of somatic inhibition disengages hippocampal dynamics from self-motion - Dard, Robin F; Leprince, Erwan; Denis, Julien; Rao Balappa, Shrisha; Suchkov, Dmitrii; Boyce, Richard; Lopez, Catherine; Giorgi-Kurz, Marie; Szwagier, Tom; Dumont, Théo; Rouault, Hervé; Minlebaev, Marat; et al. (eLife, 2022)
Early electrophysiological brain oscillations recorded in preterm babies and newborn rodents are initially mostly driven by bottom-up sensorimotor activity and only later can detach from external inputs. This is a hallmark of most developing brain areas, including the hippocampus, which, in the adult brain, functions in integrating external inputs onto internal dynamics. Such developmental disengagement from external inputs is likely a fundamental step for the proper development of cognitive internal models. Despite its importance, the developmental timeline and circuit basis for this disengagement remain unknown. To address this issue, we have investigated the daily evolution of CA1 dynamics and underlying circuits during the first two postnatal weeks of mouse development using two-photon calcium imaging in non-anesthetized pups. We show that the first postnatal week ends with an abrupt shift in the representation of self-motion in CA1. Indeed, most CA1 pyramidal cells switch from activated to inhibited by self-generated movements at the end of the first postnatal week, whereas the majority of GABAergic neurons remain positively modulated throughout this period. This rapid switch occurs within 2 days and follows the rapid anatomical and functional surge of local somatic GABAergic innervation. The observed change in dynamics is consistent with a two-population model undergoing a strengthening of inhibition. We propose that this abrupt developmental transition inaugurates the emergence of internal hippocampal dynamics.
Keywords: hippocampus; development; two-photon calcium imaging; inhibition; network dynamics